A cross-linked polymer solid electrolyte lithium battery formed by in-situ polymerization and a preparation method thereof
The formation of crosslinked polymer solid electrolytes in lithium-ion batteries through in-situ polymerization process, solving the safety hazards and interface compatibility problems of traditional batteries, and achieving high energy density and good battery performance.
Patent Information
- Application Number
- CN202411941818.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional lithium-ion batteries use flammable and explosive low-boiling carbonate solvents as electrolyte solutions, which poses safety risks. Moreover, the interface compatibility of solid polymer electrolytes prepared in non-in-situ processes is not ideal and cannot meet the requirements of high-energy-density batteries.
The lithium salt is uniformly dispersed in a carbonate organic solvent by using in situ polymerization process, polymer monomers and initiators are added, and the battery is injected into the battery by liquid lithium battery assembly method, and polymerization is induced by heating to form a crosslinked polymer solid electrolyte.
It realizes close contact between the electrode and the electrolyte, reduces interface side reactions, improves the safety and cycle stability of the battery, has high ionic conductivity, good mechanical strength, good thermal stability, and reduces production costs.
Smart Images

Figure CN119742443A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium battery with a cross-linked polymer solid electrolyte formed by in-situ polymerization and a preparation method thereof. Background Art
[0002] The development of lithium-ion batteries has brought great convenience to modern production and life, but traditional lithium-ion batteries generally use flammable and explosive low-boiling point carbonate solvents as the battery electrolyte solution, which has great safety risks. Especially when matched with high-voltage ternary positive electrodes, higher requirements are placed on the oxidation stability and safety of the electrolyte. Solid-state batteries are regarded as the most promising next-generation lithium-ion batteries due to their good safety performance.
[0003] Solid polymer electrolytes have the advantages of good interface contact, high safety, easy manufacturing, and low cost, and have become a research hotspot for the next generation of solid-state lithium batteries. In the past, the research on solid polymer lithium batteries has evolved from simple polyethylene oxide to carefully designed multilayer molecular structures through different molecular designs, including copolymerization, cross-linking, grafting, etc. These strategies have been fruitful, but their solid polymer electrolytes are usually prepared on a diaphragm and then assembled into the battery as a composite of electrolyte and diaphragm (this strategy of using a separately prepared solid polymer electrolyte to manufacture solid polymer lithium batteries is called: non-in-situ process), which will undoubtedly make the solid / solid interface compatibility between the electrolyte and the positive and negative electrodes unsatisfactory, and is incompatible with existing battery production lines, and cannot be further expanded in production scale. In addition, the thickness of the solid polymer electrolytes prepared by the non-in-situ process is mostly more than 100 microns, which is much larger than the thickness of traditional liquid electrolytes and diaphragms, and cannot meet the requirements of high energy density batteries. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a solid polymer electrolyte with good interface contact, high ionic conductivity, good mechanical strength, good thermal stability, and good compatibility with graphite negative electrode, and provides a solid polymer electrolyte lithium battery with higher energy density.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0007] S1. Evenly dispersing lithium salt in a carbonate organic solvent, adding additives, and mixing evenly to obtain a mixed solution;
[0008] S2, uniformly dispersing the polymer monomer in the above mixed solution, adding an initiator, and mixing uniformly to obtain a precursor solution;
[0009] S3. Assemble the battery according to the assembly method of the liquid lithium battery, assemble the battery in the order of the positive electrode shell, the spring, the gasket, the positive electrode, the diaphragm, the negative electrode and the negative electrode shell, inject the precursor solution as the electrolyte, and then compact it through the sealing machine. After the assembly, let it stand for 24 hours until the electrode is completely wetted, wherein the assembly method of the liquid lithium battery is the prior art;
[0010] S4, heating after standing, the added initiator induces free radical polymerization of the polymer monomer to form a polymerized solid electrolyte, and then a solid electrolyte lithium battery is obtained.
[0011] The concentration of the lithium salt in step S1 is 1.2 mol / L.
[0012] The carbonate organic solvent added in step S1 is a mixture of ethyl methyl carbonate (EMC for short), diethyl carbonate (DEC for short) and ethylene carbonate (EC for short), and the volume ratio of the three is 1:1:1.
[0013] The lithium salt added in step S1 is at least one of lithium hexafluorophosphate (abbreviated as LiPF6), lithium tetrafluoroborate (abbreviated as LiBF4), lithium bis(oxalatoborate) (abbreviated as LiBOB), lithium difluorooxalatoborate (abbreviated as LiDFOB), lithium bis(fluorosulfonyl)imide (abbreviated as LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (abbreviated as LiTFSI).
[0014] The additive added in step S1 is at least one of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, and the added amount is 5%-20% of the volume of the mixed solution.
[0015] The polymer monomer added in step S2 is one of pentaerythritol glycidyl ether (abbreviated as PEE), pentaerythritol triacrylate (abbreviated as PETA), ethylene glycol diacrylate (abbreviated as PEGDA), ethoxylated trimethylolpropane triacrylate (abbreviated as ETPTA), N,N'-methylenebisacrylamide (abbreviated as MBA), and methyl methacrylate (abbreviated as MMA).
[0016] The amount of polymer monomer added in step S2 is 1-5% of the mass of the mixed solution prepared in step S1.
[0017] The initiator added in step S2 is azobisisobutyronitrile, and the amount added is 0.5% of the mass of the mixed solution prepared in step S1.
[0018] In step S4, the standing time is 1-24 hours, the heating temperature is 50-80° C., and the heating time is 0.5-4 hours.
[0019] A cross-linked polymer solid electrolyte lithium battery formed by in-situ polymerization according to the preparation method.
[0020] The technical solution of the present invention has the following advantages:
[0021] A. The present invention achieves close contact between the electrode and the electrolyte through an in-situ polymerization process, reduces interfacial side reactions, effectively inhibits the generation of lithium dendrites, and improves the safety and cycle stability of the battery.
[0022] B. The cross-linked polymer solid electrolyte prepared by the present invention has the advantages of strong lithium ion conductivity, good high and low temperature performance, cheap raw materials, and simple synthesis.
[0023] C. The present invention optimizes the formula design of the precursor solution and the skeleton material to prepare a solid polymer electrolyte with excellent mechanical strength and thermal stability, which meets the requirements of using the battery under harsh conditions such as high strength and high temperature.
[0024] D. The present invention uses an in-situ polymerization process, which improves the interface compatibility between the solid polymer electrolyte and the electrode and significantly improves the performance of the solid polymer electrolyte lithium battery. In addition, the in-situ polymerization process eliminates the complex processes of polymer dissolution, film drying and electrolyte expansion in the non-in-situ polymerization process. It allows the synthesis of the solid polymer electrolyte and battery assembly to proceed simultaneously, effectively reducing costs and being compatible with the existing battery industry system.
[0025] E. The solid polymer electrolyte provided by the present invention has good compatibility with the nickel-cobalt-manganese ternary positive electrode, so that the battery can be matched with a positive electrode material with higher energy density, thereby improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram of the results of different polymer monomers in the present invention;
[0028] Figure 2 This is a diagram of a direct combustion test of a solid electrolyte in Example 6 of the present invention;
[0029] Figure 3 This is a schematic diagram of the electrode-electrolyte cross section of the NCM811 battery in Example 6 of the present invention;
[0030] Figure 4ion migration number test diagrams of Example 11 and Example 6 of the present invention;
[0031] Figure 5 This is a rate performance test diagram of the NCM811||Gr battery of Example 6, Example 11 and Example 12 of the present invention;
[0032] Figure 6 The graph is a cycle performance diagram of NCM811||Gr battery prepared with traditional liquid electrolyte, Example 6 and Example 12 of the present invention under a high voltage of 4.5V. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0036] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1.2 mol of LiPF6, stir until the lithium salt is dissolved, add propylene carbonate, mix well, and obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volume of the added propylene carbonate is 5% of the volume of the mixed solution;
[0037] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0038] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0039] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0040] Example 2
[0041] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0042] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1.2 mol of LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, mix well, and obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volume of the added propylene carbonate is 5% of the volume of the mixed solution;
[0043] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0044] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0045] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0046] Example 3
[0047] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0048] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, mix well, and obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volume of the added propylene carbonate is 5% of the volume of the mixed solution;
[0049] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0050] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0051] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 60°C for 0.5 hours to obtain a polymer solid electrolyte lithium battery.
[0052] Example 4
[0053] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0054] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiFSI, stir until the lithium salt is dissolved, add propylene carbonate, mix well, and obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volume of the added propylene carbonate is 5% of the volume of the mixed solution;
[0055] S2, adding 1% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0056] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0057] S4. After assembling the battery, let it stand for 4 hours, and then heat it at 70°C for 4 hours to obtain a polymer solid electrolyte lithium battery.
[0058] Example 5
[0059] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0060] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate and 1,3-propane sultone, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate and 1,3-propane sultone added are 5% of the volume of the mixed solution respectively;
[0061] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0062] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0063] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 50°C for 2 hours to obtain a polymer solid electrolyte lithium battery.
[0064] Example 6
[0065] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0066] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0067] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0068] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0069] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0070] Example 7
[0071] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0072] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0073] S2, adding 2.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0074] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0075] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0076] Example 8
[0077] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0078] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0079] S2, adding 1.5% by weight of pentaerythritol glycidyl ether to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0080] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0081] S4. After assembling the battery, let it stand for 12 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0082] Example 9
[0083] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0084] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of the added 1,3-propane sultone, diphenyldioxysilane and ethyl acetate are 5% of the volume of the mixed solution respectively;
[0085] S2, adding 1.5% by weight of ethylene glycol diacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0086] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0087] S4. After assembling the battery, let it stand for 18 hours, and then heat it at 50°C for 0.5 hours to obtain a polymer solid electrolyte lithium battery.
[0088] Example 10
[0089] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0090] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0091] S2, adding 1.5% by weight of methyl methacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0092] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0093] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0094] Embodiment 11
[0095] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0096] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0097] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0098] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0099] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0100] Example 12
[0101] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0102] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0103] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0104] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0105] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0106] Embodiment 13
[0107] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0108] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0109] S2, adding 2.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0110] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0111] S4. After assembling the battery, let it stand for 12 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0112] Embodiment 14
[0113] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0114] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0115] S2, adding 4% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0116] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0117] S4. After assembling the battery, let it stand for 8 hours, and then heat it at 70°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0118] Embodiment 15
[0119] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0120] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0121] S2, adding 5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0122] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0123] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 60°C for 1 hour to obtain a polymer solid electrolyte lithium battery.
[0124] Example 16
[0125] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0126] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0127] S2, adding 3.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0128] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0129] S4. After assembling the battery, let it stand for 6 hours, and then heat it at 80°C for 4 hours to obtain a polymer solid electrolyte lithium battery.
[0130] Embodiment 17
[0131] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0132] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0133] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0134] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0135] S4. After assembling the battery, let it stand for 24 hours, and then heat it at 70°C for 2 hours to obtain a polymer solid electrolyte lithium battery.
[0136] Embodiment 18
[0137] This embodiment provides a method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, comprising the following steps:
[0138] S1. Prepare a solution of EC, DEC and EMC in a volume ratio of 1:1:1, add 1 mol LiPF6 and 0.2 mol LiTFSI, stir until the lithium salt is dissolved, add propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, mix well to obtain a mixed solution, wherein the volume of the mixed solution is 1 L, and the volumes of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate added are 5% of the volume of the mixed solution respectively;
[0139] S2, adding 1.5% by weight of pentaerythritol triacrylate to the solution prepared in S1, adding 0.5% by weight of azobisisobutyronitrile, and mixing well to obtain a precursor solution;
[0140] S3, injecting the mixed solution into the button battery, and the whole process is completed in an inert gas;
[0141] S4. After assembling the battery, let it stand for 1 hour, and then heat it at 80°C for 4 hours to obtain a polymer solid electrolyte lithium battery.
[0142] Figure 1 Schematic diagram of different polymer monomers of the present invention. When an initiator is added to the polymer monomer, the double bonds of the polymer monomer are broken and polymerized, and the electrolyte is transformed into a solid state.
[0143] Figure 2 This is a direct combustion test of the solid electrolyte of Example 6 of the present invention. It can be seen that the solid electrolyte of Example 6 exhibits a high degree of non-flammability.
[0144] Figure 3 This is a schematic diagram of the electrode-electrolyte cross section of the NCM811 battery in Example 6 of the present invention. It shows the morphological characteristics of the close fit between the electrode and the electrolyte in the battery of the solid electrolyte formed by in-situ polymerization, reflecting the good contact between the electrolyte and the electrode.
[0145] Figure 4 is the ion migration number of Example 11 and Example 6 in the present invention. Example 11 and Example 6 have ion migration numbers of 0.51 and 0.71 respectively. Due to the in-situ polymerization of PETA, the ion migration number of the battery changes with the increase of the amount of PETA. When the content of PETA is high, too much polymer is formed to hinder the transmission of lithium ions.
[0146] Figure 5 The figure shows the rate performance of the NCM811||Gr battery of Example 6, Example 11 and Example 12 of the present invention. In the range of 0.1C to 5C, the battery using Example 6 as the electrolyte has a higher reversible capacity, while the capacity decrease in Example 11 is more obvious, which is mainly due to the excessive polymer skeleton in Example 11, which increases the internal resistance and affects the lithium ion transmission.
[0147] Figure 6 The figure shows the cycle performance of the traditional liquid electrolyte, Example 6 and Example 12 of the present invention in the NCM811||Gr battery under 4.5V high voltage. The traditional liquid electrolyte more significantly reflects the incompatibility with the NCM811||Gr high voltage system. The capacity drops rapidly during the 1C cycle and fails to work properly after 200 cycles. Example 6 has the best capacity retention rate and can still maintain 93.6% of the specific capacity after 100 cycles. In contrast, Example 12 has a lower capacity throughout the whole process.
[0148] In-situ polymerization is a method of pre-mixing liquid monomers, lithium salts, polymer initiators and other components of the electrolyte system and then carrying out a polymerization reaction from liquid phase to solid phase inside the battery after injection. It can make the interface compatibility between the solid polymer electrolyte and the electrode better, and significantly improve the performance of the solid polymer electrolyte battery. In addition, the in-situ polymerization process eliminates the complex processes of polymer dissolution, film drying and electrolyte swelling in the non-in-situ polymerization process. It enables the synthesis of solid polymer electrolytes and battery assembly to proceed simultaneously, effectively reducing costs, and is compatible with the existing battery industry system, with good application prospects.
[0149] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization, characterized in that: The steps include: S1. Evenly dispersing lithium salt in a carbonate organic solvent, adding additives, and mixing evenly to obtain a mixed solution; S2, uniformly dispersing the polymer monomer in the above mixed solution, adding an initiator, and mixing uniformly to obtain a precursor solution; S3. Assemble the battery according to the assembly method of the liquid lithium battery, assemble the battery in the order of positive electrode shell, spring sheet, gasket, positive electrode, diaphragm, negative electrode and negative electrode shell, inject the precursor solution as electrolyte, and then compact it through the sealing machine. After assembly, let it stand for 24 hours until the electrode is completely wetted; S4, heating after standing, the added initiator induces free radical polymerization of the polymer monomer to form a polymerized solid electrolyte, and then a solid electrolyte lithium battery is obtained.
2. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The concentration of the lithium salt in step S1 is 1.2 mol / L.
3. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The carbonate organic solvent added in step S1 is a mixture of ethyl methyl carbonate, diethyl carbonate and ethylene carbonate, and the volume ratio of the three is 1:1:
1.
4. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The lithium salt added in step S1 is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethyl)sulfonyl imide.
5. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The additive added in step S1 is at least one of propylene carbonate, 1,3-propane sultone, diphenyldioxysilane and ethyl acetate, and the added amount is 5%-20% of the volume of the mixed solution.
6. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The polymer monomer added in step S2 is one of pentaerythritol glycidyl ether, pentaerythritol triacrylate, ethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, N,N'-methylenebisacrylamide, and methyl methacrylate.
7. The method for preparing a cross-linked polymer solid electrolyte lithium battery by in-situ polymerization according to claim 1, characterized in that: The amount of polymer monomer added in step S2 is 1-5% of the mass of the mixed solution prepared in step S1.
8. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The initiator added in step S2 is azobisisobutyronitrile, and the amount added is 0.5% of the mass of the mixed solution prepared in step S1.
9. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: In step S4, the standing time is 1-24 hours, the heating temperature is 50-80° C., and the heating time is 0.5-4 hours.
10. A cross-linked polymer solid electrolyte lithium battery formed by in-situ polymerization according to the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of in-situ polymerization semi-solid electrolyte with gradient concentration distribution
CN121460700A